Nim's island - Orr, Wendy, 1953-; Millard, Kerry (New York : Yearling Books, 2008)
Nim loves her island home and the animals she shares it with even while her scientist father is away doing research, but trouble is on the way and a new e-mail friend could be the only one who can help.
Keywords: Electronic mail messages -- Juvenile fiction; Islands -- Juvenile fiction; Shipwreck survival -- Juvenile fiction; Missing persons -- Juvenile fiction; Sea lions -- Juvenile fiction; Iguanas -- Juvenile fiction; Sea turtles -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Friendship -- Juvenile fiction; Sea lions -- Fiction; Email -- Fiction; Islands -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Missing persons -- Fiction; Iguanas -- Fiction; Sea turtles -- Fiction; Fathers and daughters -- Fiction; Friendship -- Fiction